Resistance-capacitance dynamic model for hydrogen storage in metal hydrides with phase change material as thermal management system - Bilal Lamrani; Rubayyi T. Alqahtani; Abdelhamid Ajbar; Tarik Kousksou (Energy Conversion and Management: X)
The present work aimed at developing a novel simplified model to predict the dynamic behavior of metal hydrides (MH) reactor integrated with phase change material (PCM) for thermal regulation. This model is based on an analogy between electrical and heat transfers, where energy and mass balances are used to analyze the interactions between the hydrogen storage material, PCM, and the surrounding environment through a network of resistances. The accuracy of the proposed model is carried through comparing our numerical results with experimental data from the literature and a good agreement is obtained. A detailed parametric study is carried out where the effect of several parameters such as the hydrogen pressure, the PCM properties and its amount on the MH performances is presented and analyzed. Results show that using PCM in MH reactors has an efficient role in recovering generated heat and stabilizing the MH bed temperature. It was also shown that increasing the absorption pressure from 8 bar to 14 bar reduces hydrogenation time by approximately 39 %. Furthermore, enhancing the PCM thermal conductivity from 0.2 to 2 W/mK accelerates the hydrogen absorption process by about 67 %. While increasing PCM quantities is often recommended, this study highlights the importance of balancing PCM amount, as excessive PCM delays hydrogenation and negatively affects MH performance.